Post-War Detraumatisation Phenomenon - Abazović, Mirsad D. (Kriminalističke teme, 2002)
Each social phenomenon should not be viewed in statistical, but in dynamic sense. That applies to torture and trauma as well as help to victims of torture and violence, actually, to traumatized persons. Cause of torture, subjects and objects of torture, meaning and sense of consequences of tortures and existence of traumatized persons, needs to be observed in various levels. However, analysis of this phenomenon requires interdisciplinary approach. And in social healing of traumatization, all different disciplines need to be involved. Traumatisation should be viewed through its essence (what it actually is, what is the content, extent, complexity etc) as well as from the aspects of duration. The problem is not essence of traumatism, if the condition is only based on that. There are different mechanisms and different institutions that can successfully and ejfectively conduct and realize mission of detraumatisation. Anyhow, problem occurs due to different social conditions, when we have continuous traumatism or retraumatisatism of already traumatized persons. When we speak of this phenomenon, we refer to trauma that is consequence of past aggression and war in Bosnia and Herzegovina.